Restorative treatments with infiltrative resins and porcelain veneers in patients with dental hypoplasia: Literature review - Espinoza Cueva , Ana Daniela (2024)
Hypoplasia is a defect in the development of dental enamel that presents with various alterations in translucency, morphology, and color. The affected teeth can cause sensitivity in patients, are more prone to developing cavities, and present aesthetic problems. To address these issues, minimally invasive treatment alternatives are available, such as restorations with infiltrative resins in pediatric patients and the use of porcelain veneers in adult patients. Recognizing the causes of dental hypoplasia is essential to mitigate the progression of the enamel development defect and to determine appropriate restorative treatments. This study aimed to evaluate restorative treatments using infiltrative resins and porcelain veneers in patients with dental hypoplasia. An investigative/descriptive method was used to identify bibliographic sources on dental hypoplasia and restorative treatments. The findings demonstrated a high success rate for both types of restorative treatments, with infiltrative resins being effective for non-cavitated lesions and porcelain veneers being suitable for moderate lesions. Porcelain veneers and infiltrative resin treatments are recommended for patients with dental hypoplasia because they adhere properly and restore functionality and aesthetics to the affected teeth. Both treatments offer long-lasting results and protect the tooth from sensitivity.